The potency of green grass jelly extract (Premna oblongifolia Merr) as antihyperlipidemia towards aorta histopathology representation of rat (Rattus norvegicus) induced with high fatty diet (HFD) - Winthoko, Eka Nora Vitaloka Aprilia Putri; Roosdiana, Anna; Pratama, Dyah Ayu Oktaviani A; Nugraha, Jusak; Purwanta, Marijam; Rifa’I, Muh Husni; Rendy, Achmad Nur (Jurnal Teknologi Laboratorium, 2020)
Green grass jelly (Premna oblongifolia merr) is a plant containing fiber and chlorophyll which can lower cholesterol and triglyceride levels. This study have aims to investigate the potency of green grass jelly extract (Premna oblongifolia Merr) to prevent hyperlipidemia. The animal mode used for this study is male Rattus norvegicus, Wistar strain, the age of 8 weeks, and weight of 200 g which is divided into 5 groups of treatment namely group Kn (negative control), Kp (positive control), Kp1, Kp2, and Kp3 induced with HFD and green grass jelly extract at a dose of 5.27 g/ kg BW/ daily, 8.43 g/ kg BW/ daily, 9.37 g/ kg BW/ daily. The data of infiltrating fatty cells and macrophage on aorta histopathology was analyzed by description. This research showed that the treatment of green grass jelly extract (Premna oblongifolia Merr) to animals of hyperlipidemia model reduced infiltration fatty cells and macrophage. The conclusion of this study was the green grass jelly extract was able to prevent an increase of fatty cells and macrophage infiltration of rat (Rattus noervegicus) induced with HFD on dose 9.37 g/ kg/ BW/ daily.